Spiritual Healing Across Traditions: A Transpersonal Review of Islamic an Hindu Approaches to Psychosocial Rehabilitation - Zaduqisti, Esti; Ula, Miftahul (Journal of Sufism and Psychotherapy, 2025)
Psychosocial rehabilitation for individuals with schizophrenia typically addresses social skills, vocational training, and symptom management, yet often overlooks the spiritual dimension of recovery. Transpersonal spiritual therapy—which integrates spiritual or religious practices into psychotherapy—has emerged as a promising approach to fulfill patients’ spiritual needs alongside psychosocial goals. This literature review expands previous analyses by comparing two faith-based transpersonal interventions: Islamic Asma’ therapy and Hindu Sekala-Niskala therapy. Drawing on research from 2020– 2025 and earlier foundational studies, we examine the philosophical underpinnings, therapeutic processes, and clinical outcomes of each approach. Both frameworks emphasize connecting with a higher power to promote inner peace, meaning, and personal growth, aligning closely with transpersonal psychology’s focus on experiences beyond the ego. Case studies and recent trials indicate that integrating spiritual practices (e.g. dhikr meditation, prayer, yoga, melukat cleansing rituals) into rehabilitation can reduce psychopathology, enhance coping, and improve quality of life for people with serious mental illness. Findings show that while theological content differs, both religious frameworks offer transpersonal techniques that support recovery and complement conventional treatment.